Instrument Choice when Regulators are Concerned about Resource Extinction - Lars Gårn Hansen; Frank Jensen; Clifford Russell (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2011)
In this paper we undertake a systematic investigation of instrument choice when preventing a population collapse rather than maximizing industry profit is the overriding concern. Contrary to what seems to be the general consensus we find that landing fees do provide more effective insurance against extinction than quotas under more or less the same conditions as those implying that landing fees are better at maximising industry profit. Thus, the efficiency of the regulatory instrument mainly depends on the basic information asymmetries characterizing the fishery, and is not sensitive to whether the regulators total catch goals are set according to economic or precautionary principles.
Keywords: 330